Better luck next time : a novel - Johnson, Julia Claiborne (Custom House, 2021)
"The long anticipated second novel from the bestselling author of Be Frank With Me, set in 1930s Reno, in which two very different women seeking divorces meet and form an unlikely friendship that is complicated by the handsome young ranch hand who befriends both--and who finds his life unexpectedly upturned by one"--